Development of a Hybrid Learning Model With Interactive Multimedia Materials of Grade VII Floor Gymnastics of Mtsn 1 Malang City - Anik Hidayati; Muarifin Muarifin; Sapto Adi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The importance of a teacher choosing educational materials that are appropriate to the stage of student development and the conditions of the learning environment so that the learning process runs smoothly. Learning that intends to achieve learning objectives is designed and planned using a framework or pattern called learning media. To arouse students' interest in the learning process can be done by choosing the right learning resources. The purpose of this study was to create and test a hybrid learning tool that would assist teachers in using floor exercise learning materials. Research and Development (R&D) techniques will be used in this research and development process. As the name suggests, the ADDIE Development Research paradigm development media is an involving paradigm. Based on the research findings, interactive multimedia learning media is very helpful for students to apply hybrid learning models because with these media students can see videos independently without depending on teachers or other friends' help.